Answer:
be rewritten as a square of a sum
Step-by-step explanation:
The answer is 2. hope thishelps
Because the divider and dividend are actually smaller then factors
Answer:
D(- 1) = 2
Step-by-step explanation:
To evaluate D(- 1), substitute x = - 1 into D(x) , that is
D(- 1) = (- 1)² - 2(- 1) - 1 = 1 + 2 - 1 = 2
If the zeros are -2 and 3, then the factored form would be
(x+2) and (x-3)
-2+2 = 0 and 3-3 = 0
A polynomial is written as ax^2 + bx + c
Expand (x+2) (x-3) using FOIL: Multiply each tern in one set of parenthesis by each term in the other set and then simplify by combining like terms:
x*x + x*-3 + 2*x + 2*-3
x^2 -3x + 2x -6
Polynomial in standard form:
x^2 -x -6